PENGARUH PROFITABILITAS, LIKUIDITAS, SALES GROWTH, OPERATING CAPACITY DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS - Miftahul Sholikhah; Nur'aini Rokhmania (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of profitability, liquidity, sales growth, operating capacity and company size on financial distress. The research population is tourism companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The research sample was determined based on purposive sampling with the results of 66 companies experiencing financial distress while 14 companies did not experience financial distress. The analytical method uses logistic regression and the findings show that profitability, liquidity and operating capacity have an effect on financial distress, while sales growth and company size have no effect on financial distress.